Detection of Helicobacter pylori CagA gene and Its Association with Endoscopic Appearance in Balinese Dyspepsia Patients - I Ketut Mariadi; I Dewa Nyoman Wibawa; Ida Bagus Nyoman Wibawa (The Indonesian Society for Digestive Endoscopy, 2016)
Background: Helicobacter pylori (H. pylori) infection causes various abnormalities in the stomach. Only particular strain can cause severe problems in the stomach. CagA is a microbial virulent factor which is associated with more severe stomach problems, such as: peptic ulcer and stomach cancer. We would like to know the prevalence of CagA in Balinese population, and the association of H. Pylori CagA status with the severity of endoscopic appearance in dyspepsia patients.Method: Study design being used was analytic cross sectional study, involving 71 dyspepsia patients who underwent upper gastrointestinal endoscopic examination in Surya Husada Hospital and Balimed Hospital in June-December 2013. Sample was chosen in consecutive manner. Later, polymerase chain reaction (PCR) examinations of the stomach mucous biopsy tissue to determine H. pylori infection status and CagA status were performed. Further, Chi square test was used to identify the difference in proportion of H. pylori and CagA between mild and severe endoscopic appearance.Results: In this study, we found that the prevalence of H. pylori infection was 22.5% using PCR examination. Prevalence of CagA positive in H. pylori positive was 62.5%. There was significant association between status of H. Pylori infection and severity of endoscopic appearance (p = 0.038; OR= 2.67; 95% CI = 1.18-6.05). Status of CagA in H. pylori infected patients was not associated with the severity of endoscopic appearance. Additionally, there was significant association between patients’ age and severity of endoscopic appearance.Conclusion: The prevalence of CagA in H. pylori positive was 62.5%. H. pylori infection was associated with severity of endoscopic appearance and CagA status in H. pylori infected patients was not associated with severity of endoscopic appearance.